To multiply the polynomials \( (3x - 1)(2x + 4) \), we can use the distributive property (also known as the FOIL method for binomials).
- First Terms: \( 3x \cdot 2x = 6x^2 \)
- Outer Terms: \( 3x \cdot 4 = 12x \)
- Inner Terms: \( -1 \cdot 2x = -2x \)
- Last Terms: \( -1 \cdot 4 = -4 \)
Now, we combine all the results:
\[ 6x^2 + 12x - 2x - 4 \]
Now combine the like terms (\( 12x - 2x \)):
\[ 6x^2 + 10x - 4 \]
Therefore, the product of the polynomials \( (3x - 1)(2x + 4) \) is:
\[ \boxed{6x^2 + 10x - 4} \]